2021
DOI: 10.1093/occmed/kqab141
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social contacts on SARS-CoV-2 exposure among healthcare workers

Abstract: Background Healthcare workers (HCWs) have an increased risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection due to occupational exposure. Strict measures generally focus on the patient-to-HCW contacts. However, interactions between the HCWs also pose a high risk for SARS-CoV-2 exposure. Aims This study was aimed to investigate the effect of social contacts on the level of SARS-CoV-2 exposure risk amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
4
11
0
Order By: Relevance
“…Working in a COVID-19 designated or in an HRIU department does not increase the risk of contracting SARS-CoV-2 infection: in all three waves, HCWs in LRIUs showed a nonsignificant higher frequency of COVID-19 cases than HCWs in HRIUs (8.7% vs. 7.9%). This finding, in line with recent studies, confirms the effectiveness of the use of adequate PPE in departments dedicated to the assistance and care of patients affected by COVID-19 or at a high biological risk, such as departments where invasive and aerosol-generating procedures are carried out [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…Working in a COVID-19 designated or in an HRIU department does not increase the risk of contracting SARS-CoV-2 infection: in all three waves, HCWs in LRIUs showed a nonsignificant higher frequency of COVID-19 cases than HCWs in HRIUs (8.7% vs. 7.9%). This finding, in line with recent studies, confirms the effectiveness of the use of adequate PPE in departments dedicated to the assistance and care of patients affected by COVID-19 or at a high biological risk, such as departments where invasive and aerosol-generating procedures are carried out [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…In our analysis, we observed that more HCP were exposed when the source was a patient than a coworker (3.4 vs 2.2 HCP exposed per source, respectively), while the more significant exposures (high risk) were more common when the source was a coworker. This finding is consistent with the previously reported results by Emecen et al and Maltezou et al 5 8…”
Section: Discussionsupporting
confidence: 94%
“…Similar to previously published studies,2 3 8 our cohort demonstrated the increased risk of developing COVID-19 infection after occupational exposure to a patient or coworker source with an overall post exposure infection rate of 4.5%. While the occupational risk of SARS-CoV-2 infection in HCP has been well defined in other studies,2 4 the difference in risk from occupational exposures to different source types has been inconsistent, with some studies reporting increased infection rates following exposures to patient sources9 10 while others have found an increased occupational exposure risk from infected coworkers 5 11 12. HCP in our study were three times more likely to test positive after an exposure to a coworker vs a patient, consistent with the previously reported result by Fell et al demonstrating a postexposure conversion rate of 3.8% when the source was a coworker compared with 1.3% for a patient source 11…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…4 Frontline health-care workers (HCWs) fighting against COVID-19 infection with highly contagious and increased risk of infection due to occupational eISSN (Online): 2598-0580 exposure. 5,6 To fight against the pandemic and avoid virus transmission, HCWs must wear adequate personal protective equipment (PPE), including medical or N95 masks, goggles or face shields, coverall gowns, and gloves and perform frequent handwashing to prevent nosocomial infection as recommended by WHO. 7,8 However, performing hand hygiene frequently and prolonged application of PPE increased pressure, shear, friction, and moisture at the skin interface, leading to stratum corneum breakdown.…”
Section: Introductionmentioning
confidence: 99%